Functional Organization and Adaptability of a Decision-Making Network in Aplysia - Nargeot, Romuald; Simmers, John A. (Frontiers in Neuroscience, 2012)
Whereas major insights into the neuronal basis of adaptive behavior have been gained from the study of automatic behaviors, including reflexive and rhythmic motor acts, the neural substrates for goal-directed behaviors in which decision-making about action selection and initiation are crucial, remain poorly understood. However, the mollusk Aplysia is proving to be increasingly relevant to redressing this issue. The functional properties of the central circuits that govern this animal's goal-directed feeding behavior and particularly the neural processes underlying the selection and initiation of specific feeding actions are becoming understood. In addition to relying on the intrinsic operation of central networks, goal-directed behaviors depend on external sensory inputs that through associative learning are able to shape decision-making strategies. Here, we will review recent findings on the functional design of the central network that generates Aplysia's feeding-related movements and the sensory-derived plasticity that through learning can modify the selection and initiation of appropriate action. The animal's feeding behavior and the implications of decision-making will be briefly described. The functional design of the underlying buccal network will then be used to illustrate how cellular diversity and the coordination of neuronal burst activity provide substrates for decision-making. The contribution of specific synaptic and neuronal membrane properties within the buccal circuit will also be discussed in terms of their role in motor pattern selection and initiation. The ability of learning to “rigidify” these synaptic and cellular properties so as to regularize network operation and lead to the expression of stereotyped rhythmic behavior will then be described. Finally, these aspects will be drawn into a conceptual framework of how Aplysia's goal-directed circuitry compares to the central pattern generating networks for invertebrate rhythmic behaviors.